1985
DOI: 10.1002/jsfa.2740360304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single and multiple waterloggings on the growth and yield of winter wheat on a clay soil

Abstract: The response of winter wheat to surface waterlogging in monoliths of clay soil in lysimeters was studied. The treatments, selected as corresponding to the most extreme likely in Britain, were: 5 days of waterlogging in October between germination and emergence; 42 days of waterlogging during tillering in January and February; and 21 days from mid-April during stem elongation. These treatments were used singly and in all combinations and were compared with a freely-drained control. During waterlogging, the oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
1

Year Published

1986
1986
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
2
35
1
1
Order By: Relevance
“…This response was reflected in the reduction in grain weight, which is not consistent with the results of Belford et al (1985), who reported that waterlogging at the jointing stage reduced yield through decreased grain number per spike. In the present study, the reduction in1000-grain weight by waterlogging at the jointing stage was attributed to poor accumulation of dry matter per kernel, and reduced the remobilization of stored carbohydrates from stems/leaves to grains, which is consistent with the previous reports of Jiang et al (2008) and .…”
Section: Discussioncontrasting
confidence: 93%
“…This response was reflected in the reduction in grain weight, which is not consistent with the results of Belford et al (1985), who reported that waterlogging at the jointing stage reduced yield through decreased grain number per spike. In the present study, the reduction in1000-grain weight by waterlogging at the jointing stage was attributed to poor accumulation of dry matter per kernel, and reduced the remobilization of stored carbohydrates from stems/leaves to grains, which is consistent with the previous reports of Jiang et al (2008) and .…”
Section: Discussioncontrasting
confidence: 93%
“…Slow drainage under high rainfall conditions can lead to waterlogging. The impact on yield depends on the duration of the waterlogging and the stage of crop development at which it occurs (Belford et al 1985).…”
Section: Consequences Of Restricted Rootingmentioning
confidence: 99%
“…In 2007, heavy spring rain delayed treatment application and planting until the middle of May, but cumulative rainfall during the growing season was only 302 mm (Fig. Previous studies have also reported poor germination rates for crop plants as well as tree species in waterlogged soils (Belford et al, 1985;Zaidi et al, 2004). In contrast, the 2008 growing season was characterized by heavy rainfall throughout the season which again delayed treatment application and planting until the middle of May and resulted in standing water in the low-lying area of the field for extended periods (Fig.…”
Section: Climate and Initial Soil Propertiesmentioning
confidence: 99%
“…1A). Waterlogging or saturated conditions have been reported to cause a reduction in yield of wheat, soybean, maize, and other crops around the world (Belford et al, 1985;Zaidi et al, 2004;Zhang et al, 2006;Rhine et al, 2010). 1B).…”
Section: Climate and Initial Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation